2012
DOI: 10.1039/c1np00053e
|View full text |Cite
|
Sign up to set email alerts
|

Influenza neuraminidase: A druggable target for natural products

Abstract: The imminent threat of influenza pandemics and repeatedly reported emergence of new drug-resistant influenza virus strains demonstrate the urgent need for developing innovative and effective antiviral agents for prevention and treatment. At present, influenza neuraminidase (NA), a key enzyme in viral replication, spread, and pathogenesis, is considered to be one of the most promising targets for combating influenza. Despite the substantial medical potential of NA inhibitors (NAIs), only three of these drugs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
140
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 187 publications
2
140
0
2
Order By: Relevance
“…The antiviral activities of flavonoids have been well established. Flavonoids may interfere with the influenza virus neuraminidase (Grienke et al, 2012), uptake of the virus by the host cell , or cell signaling during influenza viral replication (Sithisarn, Michaelis, Schubert-Zsilavecz, & Cinatl, 2013). Various flavonoids including flavanols and flavonols exhibit antiherpetic activities against herpes simplex virus (HSV) type 1 and 2 in vitro (Lyu, Rhim, & Park, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral activities of flavonoids have been well established. Flavonoids may interfere with the influenza virus neuraminidase (Grienke et al, 2012), uptake of the virus by the host cell , or cell signaling during influenza viral replication (Sithisarn, Michaelis, Schubert-Zsilavecz, & Cinatl, 2013). Various flavonoids including flavanols and flavonols exhibit antiherpetic activities against herpes simplex virus (HSV) type 1 and 2 in vitro (Lyu, Rhim, & Park, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as the potency of compound 6 in vitro is comparable to the results of compound 4 (Table 1), closure of the 150-loop may be dispensable for high-affinity interaction. We also note that the 150-loop is dynamic [20] and may not play a large role in the activity of the spiro compounds. Furthermore, since the 150-loop residues do not seem to engage in stabilizing interactions, we do not expect resistance development in the 150-loop region against the spiro skeleton.…”
mentioning
confidence: 98%
“…Although this heterocyclic modification in place of the guanidine group alters the strong hydrogen-bond network seen in the case of the N8-4 complex (Figure 1 c), it did not affect the inhibitory activity appreciably, thus suggesting that this modification could be useful in mitigating the anticipated poor bioavailability of compound 4, a drawback also seen in the case of zanamivir with its polar functional groups. Recent structural characterization of various NA subtypes revealed that there are additional cavities near the active site of NA, namely the 150-cavity and 430-cavity, [6,20] which have not been exploited in the design of currently available drugs. Hence, there is a growing interest in exploring these additional cavities in the design of more potent neuraminidase inhibitors.…”
mentioning
confidence: 99%
“…Spirooliganone B from the roots of Illicium oligandrum exhibits potent anti-IFA activities [82] . A multitude of secondary plant metabolites have also been recognized as potential influenza NA inhibitors [83] , and more recent ones consist of chalcones from Glycyrrhiza inflate [84] , xanthones from Polygala karensium [85] , and homoisoflavonoids from Caesalpinia sappan [86] . Additional exploration of these natural anti-influenza agents for clinical application will help widen the drug portfolio for prophylactic/therapeutic treatment of potential flu epidemics or pandemics.…”
Section: Herbal/ayurvedic Medicinesmentioning
confidence: 99%